2015
DOI: 10.1080/00029157.2014.976786
|View full text |Cite
|
Sign up to set email alerts
|

Brain Oscillations, Hypnosis, and Hypnotizability

Abstract: In this article, we summarize the state-of-science knowledge regarding the associations between hypnosis and brain oscillations. Brain oscillations represent the combined electrical activity of neuronal assemblies, and are usually measured as specific frequencies representing slower (delta, theta, alpha) and faster (beta, gamma) oscillations. Hypnosis has been most closely linked to power in the theta band and changes in gamma activity. These oscillations are thought to play a critical role in both the recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 79 publications
(102 reference statements)
4
65
1
Order By: Relevance
“…Cumulatively, these studies seem to suggest that highly suggestible individuals exhibit reduced frontal connectivity, although further research is needed to clarify the oscillatory specificity of these effects. Multiple studies have suggested that variability in hypnotic suggestibility is associated with inter-individual differences in theta and gamma oscillations (Jensen, Adachi, & Hakimian, 2015), although these results are not yet sufficiently reliable to qualify as a neural marker of suggestibility. Nevertheless, preliminary research indicates that theta oscillatory power may predict variability in hypnotic analgesia (Jensen, Hakimian, Sherlin, & Fregni, 2008) and thus further research on the role of theta oscillations in hypnotic suggestibility is warranted.…”
Section: Neurocognitive Bases Of Hypnosis and Hypnotic Suggestibilitymentioning
confidence: 99%
“…Cumulatively, these studies seem to suggest that highly suggestible individuals exhibit reduced frontal connectivity, although further research is needed to clarify the oscillatory specificity of these effects. Multiple studies have suggested that variability in hypnotic suggestibility is associated with inter-individual differences in theta and gamma oscillations (Jensen, Adachi, & Hakimian, 2015), although these results are not yet sufficiently reliable to qualify as a neural marker of suggestibility. Nevertheless, preliminary research indicates that theta oscillatory power may predict variability in hypnotic analgesia (Jensen, Hakimian, Sherlin, & Fregni, 2008) and thus further research on the role of theta oscillations in hypnotic suggestibility is warranted.…”
Section: Neurocognitive Bases Of Hypnosis and Hypnotic Suggestibilitymentioning
confidence: 99%
“…A recent paper has argued that an increase in theta power is the common change in brain oscillations associated with hypnosis and hypnotic suggestibility (Jensen, Adachi & Hakimian, 2015). Jensen et al have proposed a theory of hypnosis and hypnotisability based on a mechanistic link between theta (and perhaps gamma) oscillations and hypnosis.…”
Section: Frontal Executive Functions and Hypnotic Suggestibilitymentioning
confidence: 99%
“…Many theories of hypnosis consider hypnosis to result in the impairment of some FEFs (Crawford & Gruzelier, 1992;Gruzelier, 2006;Jamieson & Woody, 2007;Jensen, Adachi & Hakimian, 2015;Woody & Bowers, 1994). For example, based on the Supervisory Attentional System (SAS) model (Norman & Shallice, 1986) the original Dissociated Control Theory (DCT) of hypnosis (Woody & Bowers, 1994) proposed that hypnosis disrupts the frontally-mediated SAS, leaving the participant under the guidance of contention scheduling, a process of lateral inhibition between activated neural assemblies (schemata), and therefore by schemata elicited by external cues (e.g.…”
Section: Frontal Executive Functions and Theories Of Hypnosismentioning
confidence: 99%
“…REM sleep abounds in both cortical and hippocampal theta rhythms (Cantero et al 2003). In adults, when present, theta rhythms have been associated with pleasurable feelings, drowsiness, creativity and meditative states (Schacter 1977;Gruzeler 1998;Jensen et al 2015).…”
Section: Eye Movements and Dissociative Phenomenamentioning
confidence: 99%
“…According to Gray and McNaughton (2008) theta rhythms are responsible for producing the anxiety typical of the BIS system, and are effectively silenced by many anxiolytic drugs. Other researchers, however, have connected theta rhythms to pleasurable feelings, drowsiness, creativity, and meditative states (Schacter 1977;Gruzeler 1998;Jensen et al 2015). 52 In some studies, using different brain mapping nomenclatures, the frontal eye fields have also been identified with areas 6 and/or 45 (Vernet et al 2014).…”
mentioning
confidence: 99%